HUBUNGAN FAKTOR RISIKO DENGAN ANGKA KEJADIAN INSOMNIA PADA PASIEN COVID-19 DI RSPAD GATOT SOEBROTO PADA TAHUN 2021 - Annisa Najah Ulya (2023)
Insomnia is reported as one of many sleeping difficulties occurred in COVID-19, in which insomnia or disrupted sleep were reported linked with poor outcome in infected patients recovery. There are several risk factors that may cause sleeping disruption such as sex, age, occupational status, and body mass index (BMI). The purpose of this study was to determine whether these risk factors were also associated with increased risk of insomnia in COVID-19. Methods: This research is an analytic study using cross sectional approach. Total sampling method was used for the sampling, using COVID-19 patients diagnosed from January 1, 2021 - December 31, 2021 at Gatot Soebroto Army Hospital as the research sample. Results: 141 COVID-19 patients were included in the study, divided into 2 groupings; 64 (45,4%) COVID-19 patients with sleeping trouble in the medical records and 77 (54,6%) COVID-19 without sleeping disturbance. There was relationship between age (p=0.023), sex (p=0.048), and BMI (p=0.009) and insomnia while significant correlation was not found between occupational status (p=0.488) and the incidence of insomnia. Conclusions: There were significant relationships found between age, sex, and BMI and the incidence of insomnia in COVID-19. Occupational status was not statistically linked in insomnia in COVID-19 patients. This is in line with previous studies that stated age, sex, and BMI were thought to be risk factors for insomnia in COVID-19 patients.